Impact of a simplified treatment protocol for moderate acute malnutrition with a decentralized treatment approach in emergency settings of Niger - Sánchez-Martínez, Luis Javier; Charle-Cuéllar, Pilar; Gado, Abdoul Aziz; Dougnon, Abdias Ogobara; Sanoussi, Atté; Ousmane, Nassirou; Lazoumar, Ramatoulaye Hamidou; Toure, Fanta; Vargas, Antonio; Hernández, Candela Lucía; López-Ejeda, Noemí (Frontiers in Nutrition, 2023)
Introduction: Of the 45.4 million children under 5 affected by acute malnutrition in the world, the majority (31.8 million) are affected by moderate acute malnutrition (MAM). Its treatment is particularly complex in emergency settings such as the Diffa region in Niger. This study aims to evaluate the effectiveness and coverage of a simplified treatment protocol with Community Health Workers (CHWs) as treatment providers.Methods: This study is a non-randomized controlled trial. The control group (n=181) received the standard protocol currently used in country, delivered by nursing staff only in health centres and health posts, while the intervention group (n=483) received the simplified protocol which included nursing at health centres and CHWs at health post as treatment providers.Results: The recovery rate was higher in the simplified protocol group (99.6% vs. 79.56%, p< 0.001) recording lower time to recover and higher anthropometric gain. Treatment coverage in the intervention group increased from 28.8% to 84.9% and reduced in the control group (25.3% to 13.6%). No differences were found in the recovery rate of children treated by CHWs and nursing staff. This is a provisional file, not the final typeset article Conclusion: The outcomes using the simplified protocol exceeded humanitarian requirements and demonstrated improvements compared to the standard protocol showing that the simplified protocol could be safely provided by CHWs in an emergency context. Further research in other contexts is needed to scale up this intervention.